2000
DOI: 10.1300/j013v31n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Fertility Patterns Between Urban and Rural Women in Washington State, 1983–1984 to 1993–1994

Abstract: We use data on Washington State abortions and births for 1983-1984 and 1993-1994 to analyze trends for urban and rural women, using the demographic measures total abortion and total fertility rates. These express pacing of childbearing in a single number which is simple to calculate and interpret, and is age-standardized. We find significant urban-rural differences. Total abortion rates decline and total fertility rates increase in both areas. However, the relative magnitudes of pacing decreases in abortions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Fertility levels are higher in rural areas and small towns and lower in large cities. This pattern has been observed for the US (HEATON et al 1989;GLUSKER et al 2000), England and Wales (TROMANS et al 2008), France (FAGNANI 1991), the Netherlands (MULDER and WAGNER 2001;DE BEER and DEERENBERG 2007), Italy (BRUNETTA and ROTONDI 1991;MICHIELIN 2004), Germany and Austria (HANK 2001;KULU 2006), the Nordic countries (THYGESEN et al 2005;, the Czech Republic (BURCIN and KUČERA 2000), Poland and Estonia (VOJTĚCHOVSKÁ 2000;KULU 2005; and Russia (ZAKHAROV and IVANOVA 1996).…”
Section: Introductionmentioning
confidence: 68%
“…Fertility levels are higher in rural areas and small towns and lower in large cities. This pattern has been observed for the US (HEATON et al 1989;GLUSKER et al 2000), England and Wales (TROMANS et al 2008), France (FAGNANI 1991), the Netherlands (MULDER and WAGNER 2001;DE BEER and DEERENBERG 2007), Italy (BRUNETTA and ROTONDI 1991;MICHIELIN 2004), Germany and Austria (HANK 2001;KULU 2006), the Nordic countries (THYGESEN et al 2005;, the Czech Republic (BURCIN and KUČERA 2000), Poland and Estonia (VOJTĚCHOVSKÁ 2000;KULU 2005; and Russia (ZAKHAROV and IVANOVA 1996).…”
Section: Introductionmentioning
confidence: 68%
“…One of the earliest studies of distance traveled for abortion post Roe v. Wade found that the greater the distance from an abortion clinic, the lower the abortion rate, but acknowledged that lower abortion rates may be a function of women in more rural areas far from abortion clinics preferring not to terminate a pregnancy as well as a lack of knowledge of the availability and location of abortion providers [31]. Rural populations are less likely to support abortion under a range of circumstances than their urban counterparts [32] and studies have shown higher fertility rates paired with lower abortion rates among rural women compared to urban women in specific contexts [33]. Although rural women are underrepresented among abortion patients [3], the reasons for this are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Criminal justice agencies in rural areas generally have fewer resources and smaller budgets than those in urban localities (Weisheit et al ), including limited jail space for women, inadequate staffing to accommodate female offenders' needs (e.g., pregnancy or mental health problems), and limited financial resources to transport female defendants to other facilities (e.g., state prisons). In addition, with higher fertility rates (Fuguitt, Beale, and Reibel ; Glusker et al ) but fewer accessible child‐care or elder‐care facilities in rural than urban areas (Hofferth and Iceland ), rural females are more likely to have family care responsibilities that might increase the social costs of female incarceration and result in judges' reluctance to impose longer sentence lengths. Taken together, these practical constraints of relatively high costs and limited resources might lead rural judges to be reluctant to sentence female defendants to longer jail terms, a reluctance that in turn leads to greater gender disparities in the most rural areas.…”
Section: Discussionmentioning
confidence: 99%